Conversion as Nonperformative Speech in The Jew of Malta - Parise, Emiy (Early Theatre, 2025)
Christopher Marlowe’s The Jew of Malta presents religion and religious conversion as a tool of state power, rather than as a religious process. This play’s representation of false conversions lays bare the central paradox that plagued Reformation conversion narratives: how do you know someone has truly been converted? Marlowe’s play radically transforms acts of conversion into nonperformative speech. By staging coerced, dissembling, and honest conversions in a single play, with little ritualized action to distinguish one conversion from another, Marlowe challenges the religious work of conversion, exposing it as an early modern political tool that could be manipulated by both the state and individuals.